Digital presence as competitive advantage in brazilian banks - de Oliveira, Claudio Luis Cruz; Dubeux, Veranise (Revista ADM.MADE, 2022)
This pilot study analyzes the digital presence as a relevant dimension to build the competitive advantage of Brazilian banks, which reinforces findings of previous studies. The study also introduces the Digital Presence Index (DPI) to consolidate the digital metrics, a relevant issue to strategical decision making. The research used a qualitative and quantitative approach. Specialists were interviewed, and companies joined workshops to provide a list of relevant digital metrics. Secondary researches and databases provided a historical series of banks business results and digital presence metrics. Multiple linear regression and factorial analysis methods were used to verify the relation of the digital metrics on business outcomes. This study contributed to expand the literature of multivariate analyses and data visualization to strategical decision making applied to Digital Analytics. These paper contributions can improve the decision-making process of marketing analysts, business executives, and internet professionals. Its originality highlights are the application of multivariate analysis to measure the impact of digital variables to business results in Brazilian Bank market and a new index to consolidate digital metrics.